A Review on Potential Opportunities to Preheat the Batteries Using a Finned Solar Air Energizer to Enhance Power Quality and Thermal Management in Low-Temperature Surroundings. (16th September 2022) - Dhal, P. K.; Uma, J.; Gaur, Piyush; Prasad, D.; Depoures, Melvin Victor; Rajkumar, A.; Ramesh, M.; Patel, Praveen Bhai; Birhanu, Habtewolde Ababu
Abstract : This research study's objective is to provide a comprehensive analysis of the efforts that have been made to improve the power quality and thermal management of batteries that are operating at low temperatures. These improvements have been made by combining the utilization of conventional solar air energizer (SAE) ducts with the application of a variety of different configurations of longitudinal fins. These expanded surfaces can be found on the absorber or bottom plate surface, and they are placed in a variety of positions along the airflow channel. It does this by increasing the surface area of the typical SAH and making the flow more turbulent, both of which contribute to the improvement in performance. Several studies have been carried out to enhance the thermal efficiency of clear SAE ducts by making use of experimental fins. An effort has been made to establish the Nusselt number and the friction factor by making use of the correlations that the researchers have provided. This was performed so that the performance of various configurations of finned SAEs could be compared to one another.